University extension and teacher training in Brazil: the Zoology Summer Course - Soares, Karla D. Araujo; Jeckel, Adriana; Silva, Gabriel; Giovannetti, Victor; Mathubara, Kleber (Revista Brasileira de Extensão Universitária, 2020)
Teacher training in higher education has been relatively neglected in Brazilian universities because postgraduate programs are mainly focused on the research that students produce. However, these postgraduate students are expected to become the next university and college professors. Herein, we present the experience of the Zoology Summer Course, a university extension course organized by graduate students from the Zoology Graduate Program at the University of São Paulo, Brazil. This course was created aimed to provide graduate students with an opportunity to develop and practice their teaching skills. To understand the influences, motives, and legacy of the CVZOO on its organizers, we developed a questionnaire and evaluated the responses by focusing on elements of academic formation and prospects for a teaching career, using systematic content analysis procedures as parameters. Our results demonstrate the importance of CVZOO as a space of dialogue and interaction for professional teacher training, as well as an opportunity to exchange experiences and build professional identity. The course has also influenced other academic activities such as the organization of scientific events, mentoring experience, and publications. Lastly, we discuss the importance of teacher training in Brazilian graduate programs and propose initiatives to improve the training of future university teachers. Keywords: Graduation; Extension Course; Students; Biodiversity Extensão universitária e formação docente no Brasil: o Curso de Verão em Zoologia Resumo: A formação docente universitária tem sido bastante negligenciada em universidade brasileiras, uma vez que programas de pós-graduação focam majoritariamente na produção acadêmico-científica de seus alunos. No entanto, espera-se que os pós-graduandos sejam a próxima geração de professores universitários. Neste estudo, nós apresentamos a experiência do Curso de Verão em Zoologia da Universidade de São Paulo, Brasil. Este curso foi criado com o objetivo de proporcionar aos estudantes de pós-graduação a oportunidade de desenvolver e praticar suas habilidades para docência. No intuito de entender as influências, motivações e legado do CVZOO em seus organizadores, nós desenvolvemos um questionário e avaliamos as respostas buscando elementos da formação acadêmica e prospecção para a carreira docente, usando procedimentos de análise de conteúdo como parâmetros Os resultados demonstram a importância do CVZOO como um espaço de diálogo e interação com a prática docente bem como uma oportunidade para trocar experiências e construir uma identidade profissional. O curso tem influenciado em outras atividades acadêmicas, tais como organização de eventos científicos, orientação de alunos e publicações. Por fim, este artigo discute a importância da formação docente em programas de pós-graduação no Brasil e propõe algumas iniciativas para melhorar a formação dos futuros professores universitários. Palavras-chave: Pós-Graduação; Curso de Extensão; Estudantes; Biodiversidade